Interface Shear Strength at Joints of Ultra-High Performance Concrete Structures - Kim, Young Jin; Chin, Won Jong; Jeon, Se Jin (International Journal of Concrete Structures and Materials, 2018)
When ultra-high performance concrete (UHPC) is fabricated as precast members such as in a UHPC segmental bridge, the joint design between the precast members can significantly affect the overall integrity and safety of the structure. Therefore, the structural behavior of the UHPC joint was experimentally investigated in this study with test variables including joint type, number and height of shear keys, type of filler, curing temperature, and lateral compressive stress. The UHPC considered in this study is the K-UHPC developed in Korea with a specified compressive strength as high as 180 MPa and high flowability. The joint shear strengths affected by the test variables were investigated in detail. The test results were also compared with two representative predictive equations for interface shear strength to determine an appropriate equation for the joint design of UHPC. These equations did not match well with the test data because they were originally proposed for normal strength concrete. However, the JSCE equation could be improved by modifying a coefficient to show good agreement with the test especially in the case of the dry joint with epoxy application.
Keywords: Dry joints; Interface shear strength; Push offs; Shear key; Ultra high performance concretes; Wet joint; dry joint; interface shear strength; push-off test; shear key; ultra-high performance concrete; wet joint